A Stereoselective Glycosylation Approach to the Construction of 1, 2‐trans‐β‐d‐Glycosidic Linkages and Convergent Synthesis of Saponins. Issue 7 (22nd December 2021) - Yang, Fuzhu; Hou, Wu; Zhu, Dapeng; Tang, Yu; Yu, Biao
Abstract: Conventional syntheses of 1, 2‐ trans ‐β‐d ‐ or α‐l ‐glycosidic linkages rely mainly on neighboring group participation in the glycosylation reactions. The requirement for a neighboring participation group (NPG) excludes direct glycosylation with (1→2)‐linked glycan donors, thus only allowing stepwise assembly of glycans and glycoconjugates containing this type of common motif. Here, a robust glycosylation protocol for the synthesis of 1, 2‐ trans ‐β‐d ‐ or α‐l ‐glycosidic linkages without resorting to NPG is disclosed; it employs an optimal combination of glycosyl N ‐phenyltrifluroacetimidates as donors, FeCl3 as promoter, and CH2 Cl2 /nitrile as solvent. A broad substrate scope has been demonstrated by glycosylations with 12 (1→2)‐linked di‐ and trisaccharide donors and 13 alcoholic acceptors including eight complex triterpene derivatives. Most of the glycosylation reactions are high yielding and exclusively 1, 2‐ trans selective. Ten representative, naturally occurring triterpene saponins were thus synthesized in a convergent manner after deprotection of the coupled glycosides. Intensive mechanistic studies indicated that this glycosylation proceeds by SN 2‐type substitution of the glycosyl α‐nitrilium intermediates. Importantly, FeCl3 dissociates and coordinates with nitrile into [Fe(RCN) n Cl2 ] + and [FeCl4 ] −, and the ferric cationic species coordinates with the alcoholic acceptor to provide a protic species that activates the imidate, meanwhile the poor nucleophilicity of [FeCl4 ] − ensures an uninterruptive role for the glycosidation. Abstract : Direct action : A highly stereoselective glycosylation protocol for the synthesis of 1, 2‐ trans ‐β‐d ‐ or α‐l ‐glycosidic linkages is disclosed, which employs a combination of glycosyl N ‐phenyltrifluroacetimidates as donors, FeCl3 as promoter, and CH2 Cl2 /nitrile as solvent and exploits glycosidation via glycosyl α‐nitrilium intermediates. A variety of natural saponins containing (1→2)‐linked glycan motifs are thus synthesized in convergent manner by direct glycosylation with (1→2)‐linked glycan donors.